Extraction and Microencapsulation of Polyphenols from Orthosiphon Stamineus Leaves - Sook, Fun Pang; Mei, Zhu Lau; M. M., Yusoff; Jolius, Gimbun (Faculty Mechanical Engineering, UMP, 2014)
This paper presents an extraction and microencapsulation study of polyphenols obtained from Orthosiphon stamineus leaves. Extraction using aqueous solvent enabled a simultaneous extraction of both hydrophilic and lipophilic phenolic compounds. Higher solid concentration leads to higher solution viscosity, bigger particle size, lower moisture content and a less dented surface, which may improve particle flowability. The results suggest that eupatorin and rosmarinic acid are more susceptible to thermal degradation than sinensetin during spray drying. The formulation of 1:9 whey protein to maltodextrin ratio was also found to be more effective, with 86.7% total flavonoids retention compared to other formulations, viz, 1:1 and 9:1.